STRUKTUR KOMUNITAS FITOPLANKTON DI KAWASAN BUKIT CINTA DANAU RAWAPENING, KABUPATEN SEMARANG. - Siti Mudhakiroh; Tri Retnaningsih Soeprobowati; Fuad Muhammad; Sri Utami (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Bukit Cinta is a sub-area in Rawapening Lake, is developed tourism destination. Bukit Cinta has problems such as degradation of water quality, the sediment of upstream, blooming of water plants, waters pollution due activity of tourism. The aim of this research is an overview of environmental conditions through phytoplankton community structure. Phytoplankton samples were taken in 4 points with depth in example: 1-2m, 1-4m, 1-8m, and 1-10m. The water sample was taken by using Van Dorn water sampler, then were filtered using plankton. SRCC was used through identification phytoplankton and later was continued by calculating of abundant, diversity, uniformity, domination, saprobic indices. The result of phytoplankton observation at Bukit Cinta is 53 genus of phytoplankton that devide to 5 division Bacillariophyta (24 genus), Chlorophyta (16 genus), Cyanophyta (6 genus), Euglenophyta (4 genus), Dinoflagellata (3 genus). Species that dominated is Synechococcus elongatus Nageli (division Cyanophyta), Aulacoseira granulata and Synedra ulna (division Bacillariophyta). Species that dominated is Synechococcus elongatus Nageli (divisi Cyanophyta), Aulacoseira granulata and Synedra ulna (division Bacillariophyta). Based on diversity, evenness, domination and saprobic indices, the area that is categorized as highly disturbed is St 4 (10m depth) and less disturbed is St 3 (8m depth). Meanwhile, based on Pollution Index, the area that is categorized as highly disturbed is St 2 (4m depth) and less disturbed is St 1 (2m depth).Keywords: Bukit Cinta, Structure Community, Phytoplankton, Saprobic